HIV-1 Reservoir Dynamics after Vaccination and Antiretroviral Therapy Interruption Are Associated with Dendritic Cell Vaccine-Induced T Cell Responses - Andrés, Cristina; Plana, Montserrat; Guardo, Alberto C.; Alvarez-Fernández, Carmen; Climent, Nuria; Gallart, Teresa; León, Agathe; Clotet, Bonaventura; Autran, Brigitte; Chomont, Nicolas; Gatell, Josep M.; Sánchez-Palomino, Sonsoles; et al. (Journal of virology, 2015)
HIV-1-specific immune responses induced by a dendritic cell (DC)-based therapeutic vaccine might have some effect on the viral reservoir. Patients on combination antiretroviral therapy (cART) were randomized to receive DCs pulsed with autologous HIV-1 ( n = 24) (DC-HIV-1) or nonpulsed DCs ( n = 12) (DC-control). We measured the levels of total and integrated HIV-1 DNA in CD4 T cells isolated from these patients at 6 time points: before any cART; before the first cART interruption, which was at 56 weeks before the first immunization to isolate virus for pulsing DCs; before and after vaccinations (VAC1 and VAC2); and at weeks 12 and 48 after the second cART interruption. The vaccinations did not influence HIV-1 DNA levels in vaccinated subjects. After the cART interruption at week 12 postvaccination, while total HIV-1 DNA increased significantly in both arms, integrated HIV-1 DNA did not change in vaccinees (mean of 1.8 log 10 to 1.9 copies/10 6 CD4 T cells, P = 0.22) and did increase in controls (mean of 1.8 log 10 to 2.1 copies/10 6 CD4 T cells, P = 0.02) ( P = 0.03 for the difference between groups). However, this lack of increase of integrated HIV-1 DNA observed in the DC-HIV-1 group was transient, and at week 48 after cART interruption, no differences were observed between the groups. The HIV-1-specific T cell responses at the VAC2 time point were inversely correlated with the total and integrated HIV-1 DNA levels after cART interruption in vaccinees ( r [Pearson's correlation coefficient] = −0.69, P = 0.002, and r = −0.82, P < 0.0001, respectively). No correlations were found in controls. HIV-1-specific T cell immune responses elicited by DC therapeutic vaccines drive changes in HIV-1 DNA after vaccination and cART interruption. (This study has been registered at ClinicalTrials.gov under registration no. NCT00402142.) IMPORTANCE There is an intense interest in developing strategies to target HIV-1 reservoirs as they create barriers to curing the disease. The development of therapeutic vaccines aimed at enhancing immune-mediated clearance of virus-producing cells is of high priority. Few therapeutic vaccine clinical trials have investigated the role of therapeutic vaccines as a strategy to safely eliminate or control viral reservoirs. We recently reported that a dendritic cell-based therapeutic vaccine was able to significantly decrease the viral set point in vaccinated patients, with a concomitant increase in HIV-1-specific T cell responses. The HIV-1-specific T cell immune responses elicited by this therapeutic dendritic cell vaccine drove changes in the viral reservoir after vaccinations and significantly delayed the replenishment of integrated HIV-1 DNA after cART interruption. These data help in understanding how an immunization could shift the virus-host balance and are instrumental for better design of strategies to reach a functional cure of HIV-1 infection.